Determinação elementar e avaliação da geração química de vapor para determinação simultânea de As e Hg em suplementos alimentares por MIP OES - Bitencourt, Gustavo Rossato (2021)
In this work the suitability of microwave induced plasma optical emission spectrometry (MIP OES) for the determination of essential and non-essential elements in dietary supplements was evaluated. In this purpose, thirteen dietary supplement samples of several classifications (vitamins/minerals, minerals, amino acids, and botanicals) were digested by microwave-assisted wet digestion (MAWD) in their whole form for further determination of essential (Ca, Co, Cu, Fe, K, Mg, Mn, Mo, Na, and Zn) and non-essential (Ag, Al, B, Ba, Be, Cd, Cr, La, Li, Ni, Pb, Sr, and V) elements by MIP OES. After defining the most suitable operating conditions for MIP OES, potential interferences by major concomitants (C, Cl, Ca, K, Na, and S) were evaluated, as well as those by residual acidity of digests. The feasibility of the simultaneous determination of As and Hg by CVG-MIP OES was also evaluated, looking to obtain limits of quantification (LOQs) in compliance with maximum concentrations allowed for these elements in dietary supplements according to USP General Chapter 2232 and EC 629/2008 (only for Hg). A multimode sample introduction system (MSIS) was used, and several system setups were evaluated to improve the signal-to-noise ratio. The critical conditions for volatile species generation were optimized, as the reagents concentrations (NaBH4 and HCl), the reaction coil length, the flow-rate, and methods for the pre-reduction of As5+ to As3+. After optimizing the determination conditions, the study of interferences showed a suppression in some situations leading to a minimum dilution factor (2 and 50-fold) to samples with higher concentrations of Ca, Na, and K. The LOQs were in the range of 0.010 (Be) to 39.2 μg g-1 (Ca) and were dependent on the sample mass used for decomposition (from 0.6 to 1.6 g in the commercial product). There was a prevalence of essential and non-essential elements in vitamins/minerals, minerals, and botanicals dietary supplements, whereas lower concentrations were found in the dietary supplements of amino acids. Although the concentration of many elements was not in agreement with that which is labeled, all were in a concentration below the recommended dietary allowances (RDAs), exception for those with the concentration intentionally higher. Accuracy of results obtained by MIP OES was evaluated by comparison with those obtained by ICP OES and/or ICP-MS, with no statistical difference between them (t-test). Moreover, for the CRMs NIST 1572 and NIST 1575a, the results showed no statistical difference with the certified values (t-test). For the simultaneous determination of As and Hg by CVG-MIP OES, a suitable condition was established that led to signal improvement by 3 and 12-fold for As and Hg, respectively, compared with those intensities obtained using conventional nebulization. The LOQs obtained for As and Hg ranged from 0.058 to 0.187 and 0.126 to 0.403 μg g-1, respectively, which were below 1.5 μg g-1, limit stipulated by USP normative for both elements. Whereas the concentration of Hg in all samples was below to the LOQs, the concentration of As ranged from 0.099 to 0.274 μg g-1. The results by CVG-MIP OES presented no statistical difference with those obtained by ICP-MS for As (after decomposition by combustion) and CVG-ICP-MS, for Hg (after MAWD) (t-test). For the CRMs NIST 1572 and NIST 1575a, the results by CVG-MIP OES for As and Hg showed no statistical difference when compared to the certified values (t-test). Also, recovery tests at three concentration levels were performed for As and Hg and recoveries ranged from 93 to 108%. The MIP OES proved to be a suitable technique for the determination of essential and non-essential elements, including As and Hg by CVG-MIP OES, in dietary supplements, demonstrating to be a feasible alternative to the quality control of these products.